Special issue on early algebraic thinking / Número especial sobre el pensamiento algebraico temprano. Issue 3 (3rd July 2019) - Cañadas, María C.; Blanton, Maria; Brizuela, Bárbara M.
Abstract: In this introduction to the Special Issue Early algebraic thinking: studies from different perspectives, approaches and regions we provide readers with the main motivation and interest underlying research on early algebraic thinking. We then introduce the five papers that make up this Special Issue. Each of these studies, coming from various countries around the world, has a different theoretical framework, methodological approach and perspective regarding teachers, students, instructional practices and curricula. In this introduction, we summarize some of the main themes throughout the different papers, including interviewers' practices that can promote early algebraic thinking; the kinds of practices that teachers can implement to have a positive impact on students' early algebraic thinking; and the use of physical models to explore and promote aspects of early algebraic thinking. The Special Issue also includes an additional Prospectives piece by Analúcia Schliemann and David Carraher, in which they examine the algebraic thinking research in elementary school in light of the current mathematics standards in the United States.